Genome editing in plants via designed zinc finger nucleases - Petolino, Joseph F. (In Vitro Cell Dev Biol Plant, 2015)
The ability to create DNA double-strand breaks (DSBs) at specified genomic locations, which then stimulate the cell’s naturally occurring DNA repair processes, has introduced intriguing possibilities for genetic modification. Zinc finger nucleases (ZFNs) are designed restriction enzymes consisting of a nonspecific cleavage domain fused to sequence-specific DNA binding domains. ZFN-mediated DSB formation at endogenous genomic loci followed by error-prone non-homologous end joining (NHEJ) repair can result in gene-specific mutations via nucleotide base pair insertions or deletions. Similarly, specific DNA sequence modifications can be made by providing donor DNA templates homologous to sequences flanking the cleavage site via homology-directed repair (HDR). Targeted deletions of intervening DNA sequence can be obtained by ZFNs used to create concurrent DSBs. Site-specific transgene integration into ZFN-induced DSBs is possible via either NHEJ or HDR. Genome editing can be used to enhance our basic understanding of plant gene function as well as modify and improve crop plants. As with conventional plant transformation technology, the efficiency of genome editing is absolutely dependent on the ability to initiate, maintain, and regenerate plant cell and tissue cultures.